(untitled) (Italian Journal of Food Safety, 2017)
V. vulnificus is a Gram-negative bacterium, commonly found in estuarine and coastal habitats, that can infect humans through seafood consumption or wound exposure. This study represents the first attempt to correlate the genotype of Vibrio vulnificus strains isolated in the north-western Adriatic Sea coastal area, with their antimicrobial susceptibility patterns. On the whole, 40 V. vulnificus strains, isolated from shellfish (n=20), different coastal water bodies (n=19), and the blood of a Carretta carretta turtle (n=1), were utilized. All strains were positive for the species-specific genes vvhA and hsp, with high variability for other markers: 55% (22 out of 40) resulted of the environmental (E) genotype (vcgE, 16S rRNA type A, CPS2 or CPS0), 10% (4 out of 40) of the clinical (C) genotype (vcgC, 16S rRNA type B, CPS1), and 35% (14 out of 40) of the mixed (M) genotype, possessing both E and C markers. The antimicrobial susceptibility was assayed by the diffusion method on agar, according to the Clinical Laboratory Standards Institute (CLSI), utilizing the following commercial disks (Oxoid): ampicillin (AMP), ampicillin- sulbactam (SAM), piperacillin (PRL), cefazolin (KZ), cefotaxime(CTX), ceftazidime( CAZ), imipenem (IPM), meropenem (MEM), amikacin (AK), gentamicin(CN), tetracycline(TE), ciprofloxacin (CIP), levofloxacin (LEV), trimethoprim-sulfamethoxazole (SXT), and chloramphenicol (C). 75% of the strains, (n=30) including all C strains, was sensitive to all the tested antibiotics, whereas E strains showed intermediate sensitivity to AK (2 strains), CIP and CAZ (1 strain), TE (1 strain) and resistance to KZ (1 strain), and 4 M strains showed I to AK.